EFFECT OF COVID-19 ON EXERCISE HEALTH BELIEF, EMOTIONAL INTELLIGENCE AND STRESS LEVELS IN EMERGENCY UNIT NURSES - Mustafa DURMUŞ; Necmettin ÇİFTCİ; Halil ALKAN (Rojan GÜMÜŞ, 2021)
This study was conducted to examine the effect of COVID-19 on exercise health belief, emotional intelligence, and stress levels in emergency unit nurses. The research was carried out on 1- 30.01.2021 with 210 nurses who are working in emergency units located in five hospitals in the Eastern Anatolia region of Turkey. A significant relationship was found between the nurses' status of contracting COVID-19 and exercise belief, emotional intelligence, and perceived stress levels. While it was found that the exercise health belief and stress levels of nurses who had COVID-19 were higher than those who did not have COVID-19, it was found that the emotional intelligence levels of nurses who had COVID-19 were lower than those who did not.